The saintly politics of Catherine of Siena - Luongo, F. Thomas (Francis Thomas) (Cornell University Press, 2006)
"In The Saintly Politics of Catherine of Siena, F. Thomas Luongo combines literary-critical readings of Catherine's letters - she was the author of one of the largest collections of medieval letters - with political and social analysis